2017
DOI: 10.1097/qad.0000000000001349
|View full text |Cite|
|
Sign up to set email alerts
|

Tenofovir alafenamide and elvitegravir loaded nanoparticles for long-acting prevention of HIV-1 vaginal transmission

Abstract: Objective This report presents tenofovir alafenamide (TAF) and elvitegravir (EVG) fabricated into nanoparticles (NPs) for subcutaneous (SubQ) delivery as prevention strategy. Design Prospective prevention study in hu-BLT mice. Methods Using an oil-in-water emulsion solvent evaporation technique, TAF+EVG drugs were entrapped together into NPs containing poly(lactic-co-glycolic acid) (PLGA). In vitro prophylaxis studies (IC90) compared NPs to drugs in solution. Humanized-BLT (n=5/group) mice were given 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 27 publications
2
72
0
Order By: Relevance
“…The NPs physicochemical characterization has been reported in our earlier article (14). Briefly, the o-w emulsion methodology resulted in uniform well-defined TAF+EVG NPs having 221.6 ± 6.1 nm size, with PDI; a measure of the NP size variability of 0.107 ± 0.01 (less than < 0.2, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The NPs physicochemical characterization has been reported in our earlier article (14). Briefly, the o-w emulsion methodology resulted in uniform well-defined TAF+EVG NPs having 221.6 ± 6.1 nm size, with PDI; a measure of the NP size variability of 0.107 ± 0.01 (less than < 0.2, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously published the addition of EVG in vitro is synergistic to TFV for HIV-1 protection (14). However, further trials are appropriate in larger animal models for the ARV NPs to prove a link between tissue drug concentration and efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the sustained ART-free remission is a well-accepted and effective strategy to control HIV infection, the main focus of HIV research is to develop strategies that prolong protection and target latent HIV+ cells. Recent studies have demonstrated designing a long-acting (LA) ARV delivery system would boost the HIV prevention and treatment strategy (69). The LA ARV delivery system has shown to enhance drug-solubility, stability, biodistribution, pharmacokinetics, efficiency, and concurrent drug safety, due to reduced ARV associated side-effects, such as mitochondrial toxicity, renal abnormality, and reduced bone mineral density (10–12).…”
Section: Introductionmentioning
confidence: 99%